Effect of Breathing exercise during labour on delivery outcome: An interventional study - Shahab Hasan , Kawthar; Azez Said, Awaz (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Labor is a physically and emotionally demanding process, often accompanied by pain, anxiety, and physiological stress. Lamaze breathing techniques are evidence-based, non-pharmacological methods that promote maternal control, reduce labor discomfort, and improve delivery outcomes. This study aimed to evaluate the effect of Lamaze breathing exercise on maternal and fetal outcomes among primigravida women. Methods: A quasi-experimental design was used with a purposive sample of 118 primigravida women, who were equally divided into a study group and a control group (n = 59 each). The study group received Lamaze breathing intervention during the first and second stages of labor, while the control group received routine care. Data were collected through structured questionnaires, the perceived stress scale, and observation checklists for maternal and neonatal outcomes. Results: Results from the post-intervention revealed that the study group's stress levels had significantly decreased. (66.1% low stress vs. 0% in the control group; P <0.001), shorter second-stage labor (<30 minutes in 59.3% vs. 10.2%; P<0 .001), and higher first-minute APGAR scores (93.2% normal vs. 61.0%; P <0.001). No statistically significant differences were found in fifth-minute APGAR scores, NICU admissions, newborn weight, or maternal complications, although trends favored the intervention group. Conclusion: Lamaze breathing exercises significantly reduced maternal stress and second-stage labor duration, and improved neonatal condition at birth. Integrating such interventions into antenatal education is recommended for enhancing birth outcomes in primigravida women.